Analytical Study on Policies of Population Control In India: Examining the Impact of Population Control Policies in the Indian Context (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Population growth has long been a concern of thegovernment, and India has a lengthy history of explicit population policy. Inthe 1950s, the government began, in a modest way, one of the earliest national,government-sponsored family planning efforts in the developing world. Theannual population growth rate in the previous decade (1941 to 1951) had beenbelow 1.3 percent, and government planners optimistically believed that thepopulation would continue to grow at roughly the same rate. Implicitly, the government believed that India couldrepeat the experience of the developed nations where industrialization and arise in the standard of living had been accompanied by a drop in the populationgrowth rate. This paper discussed the policies of population and its control inIndian context.